Clin‐STAR corner: Practice changing advances in cardiology. Issue 4 (16th December 2022) - Husaini, Mustafa; Rich, Michael W.
Abstract: Although cardiovascular disease is the leading cause of death and major disability in older adults, older patients have been consistently under‐represented in most cardiovascular clinical trials. This article summarizes the results of four trials published from 2020 to 2022 with practice‐changing implications directly applicable to the care of older adults. The key findings from these trials were that: (1) an initial conservative approach to managing selected patients with stable ischemic heart disease is reasonable, even in the setting of moderate or severe ischemia; (2) empagliflozin is effective in reducing heart failure hospitalizations in patients with heart failure and preserved ejection fraction, with or without diabetes; (3) an individually tailored physical rehabilitation program reduces deconditioning and functional decline in older patients hospitalized with heart failure; and (4) restricting dietary sodium intake to less than 1500 mg/day is unlikely to improve outcomes in most patients with heart failure.